Identification and characterisation of novel SMAD2/3 binding partners underlying pancreatic cancer cell plasticity - Ervin, E-H (2022)
Pancreatic cancer is one of the deadliest malignancies in human with a 5-year survival rate of less than 10% and median survival time of 7-11 months. The most common type of pancreatic cancer is pancreatic ductal adenocarcinoma (PDAC) which accounts for more than 90% of cases, and is associated with poor prognosis due to late diagnosis, aggressive growth and therapy resistance. Accumulating evidence shows that PDAC cell is able to successfully complete metastatic cascade and survive therapeutic stress due to extraordinary cellular plasticity which is defined as a cell ability to change its phenotype. The molecular mechanisms underlying PDAC cell phenotypic plasticity are not completely understood but it is well-established that cell phenotype is largely determined by its transcriptional program. Elevated levels of transforming growth factor β (TGF-β) have been detected in PDAC tissue and intracellular effector molecules of canonical TGF-β pathway, namely SMAD2 and SMAD3, have been shown to enhance transcriptional reprogramming. Since the transcriptional program activated by SMAD2/3 is determined by the sequence-specific transcription factors that SMAD2/3 interact with, we hypothesised that the phenotype switching of PDAC cell may be mediated by SMAD2/3 switching binding partners.